Robustness of palm kernel oil blend in suppository preparation using acetaminophen as a model drug - Noordin, M.I.; Chung, Lip Yong (SAGE Publications, 2007)
Background: Theobroma oil suppository base has good characteristics for the delivery of most drugs, but its polymorphism renders it a difficult medium with which to work. Preparation of suppositories using theobroma oil must be carried out at a temperature below 36 °C to avoid formation of metastable polymorphs. Substitutes for theobroma oil are therefore desirable. Objective: To compare the characteristics of theobroma oil- and palm kernel oil blend (PKOB)-based suppositories, each produced by 2 different techniques of preparation. Methods: Theobroma oil and PKOB (consisting of hydrogenated palm kernel oil and hydrogenated palm kernel stearin in an 8:2 ratio, with 5 stearic acid and 5 glyceryl monostearate) were used as a base. Suppositories were prepared by 2 different techniques, with acetaminophen used as the model drug. The standard technique used a water bath to melt the base preparation at 36 °C before incorporation of acetaminophen, while the second technique involved melting the base in an oven at 60 °C. The 2 types of suppositories produced by these techniques were then tested physically for appearance, hardness, liquefaction time, and melting characteristics using differential scanning calorimetry. Results: Satisfactory theobroma oil-based suppositories were produced by the water bath technique at 36 °C, but the oven technique at 60 °C failed to produce a good product. On the other hand, both techniques produced satisfactory PKOB-based suppositories that were similar in both physical and thermal characteristics. Conclusions: PKOB constituted with the above-mentioned ingredients can be exposed to a wider range of temperatures without risk of polymorphism.